“Rosas da Praça”: um olhar sobre as vivências, limites e desafios das mulheres em situação de rua no município de Registro/SP - Anjos, Josefa Silvana Ferreira dos (2024)
The goal of the current thesis is to examine the social and gender disparities that are inherent in the process of studying homeless women in the city of Registro/SP. The research concentrated on women experiencing homelessness who take part in the "Rosas da Praça" Project, a social work program that has been available at the Registro Specialized Reference Center for Social Assistance (CREAS, in Portuguese) since 2021. The study's objectives were to comprehend this universe, learn about the women's life paths and narratives, and ascertain the effects of their involvement in the "Rosas da Praça" group—a social protection advocacy group—on their respective lives. It traced the homeless population as an expression of the social issue and verified whether the work of the "Rosas da Praça" Group was a space for listening, protagonism, and strategies and interventions that helped them to rescue their own identity, affirm their potential, and contribute to the transformation of the participants' social reality. In a patriarchal and sexist culture, the surroundings and the difficulties that women encounter when using the streets as a place for refuge and survival are explored and presented. The debate concerning social policies—their merits and demerits—is crucial in ensuring that this marginalized and invisible population may access social rights and potentially overcome homelessness